Treatment of Non - Complicated Lower Urinary Tract Infection in Pregnancy: Single Dose Fosfomycin Tromethamine Versus Multiple Dose Nitrofurantoin - Özel, Murat; Kaymak, Oktay; Birgili, Nüvit; Çelen, Şevki; Erdoğan, Mine; Danışman, Nuri (Gynecology Obstetrics & Reproductive Medicine, 2011)
OBJECTIVE: To evaluate the efficacy of single-dose fosfomycin tromethamine (FT) treatment in pregnant women with uncomplicated lower urinary tract infection (UTI). STUDY DESIGN: In this study, 421 pregnant women with established, symptomatic, uncomplicated lower UTI were randomly allocated to receive either a single dose of FT (Monurol®, Zambon Group S.p.A, Milan-ITALY) (n=217) or a 7-day course of nitrofurantoin (n=204). The treatment was found to be effective if urine culture was negative 15 days after therapy. RESULTS: Microbiological cure was achieved in 205 (94.5%) patients treated with FT and 164 (80.4%) patients treated with nitrofurantoin (p<0.05). Pathogen microorganisms were predominantly E.coli (199 in FT and 183 in NF group) followed by Klebsiella (18 in FT and 21 in NF group). CONCLUSION: The treatment of acut lower UTI in pregnant women is essential. FT is an effective, safe, single dose treatment choice in the management of uncomplicated lower UTI in pregnant women.